901 Risk factors for bicycling injuries in children and adolescents: a systematic review. (1st September 2016) - Embree, Tania; Romanow, Nicole; Djerboua, Maya; Morgunov, Natalie; Williamson, Jacqueline; Hagel, Brent
Abstract : Background: Bicycling injuries in young people represent a substantial cost to health care systems. The objective of this review was to examine the individual and environmental factors associated with bicycling-related injury risk in children and youth. Methods: Fourteen electronic databases were searched using exploded subject headings and keywords. Two authors independently screened article titles and abstracts for inclusion. The full-text of the potential articles was assessed to determine eligibility. The inclusion criteria were bicyclists less than 18 years old; individual and environmental characteristics of bicycling outcomes; comparisons between injured and uninjured bicyclists, injury type or severity level; study designs with a pre-determined comparison group; and publications in English from 1990 to May 2015. The exclusion criteria were injury outcomes related to helmet use, helmet legislation or mountain biking; comparisons of census-based injury rates; cross-sectional studies; and letters to the editor. A modified version of the Newcastle-Ottawa Scale was used to assess study quality. Results: Fifteen articles met the inclusion and exclusion criteria. Overall, 46 different risk factors were examined. The most commonly reported risk factors were age (N = 10 studies), sex (N = 7), equipment related factors (N = 6), bicycling exposure (N = 5), bicycling purpose (N = 5), and motor vehicle (MV) collision (N = 4). The reviewed studies varied in quality; the main weaknesses were inadequate definitions of study groups, lack of control for potential confounders, and the use of self-reported data. Conclusions: While many of the studies had significant limitations, one recurring theme was that young bicyclists received more severe injuries when exposed to MV collisions. To reduce injuries in children and adolescents, we recommend separating bicyclists from MVs on the road and implementing strategies to reduce traffic speed and volume.